Travail social dans les prisons bruxelloises : un puzzle aux nombreuses pièces - Liesbeth Naessens (Brussels Studies)
The welfare needs of detainees are often complex and difficult to fulfill because they often relate to various areas of life. By supplying assistance and services to detainees and their relatives, different organizations try to formulate an answer to these needs. This kind of assistance and services extends over various domains such as education, culture, employment, sports, health, well-being... The services for judicial welfare work are playing an important role in this matter. This contribution focuses on the specific characteristic properties of the Brussels judicial welfare work. We also discuss the results of a practice-oriented survey from the Odisee College about the way the Brussels judicial welfare work operates, its network and its collaboration with other services.